Influence of selected factors on ICT usage among education college lecturers in Kano State, Nigeria - Musa, Umar (2019)
Nigerian studies confirms that ICT lecturers in the country have low levels of ICT usage due to a lack of computers in the departments and inaccessibility to the Internet. Furthermore, poor information infrastructure accounts for low ICT development and application. Although a few studies have focused on selected factors of ICT usage, not much is known about the extent of ICT usage. This study determined the level of ICT usage and selected factors of ICT usage, such as Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), Facilitating Conditions (FC), Technological Pedagogical Content Knowledge (TPACK), and attitudes towards ICT (ATTIC). The study is a quantitative descriptive research. The research instrument was a set of questionnaires—the population of the study comprised 1775 college lecturers in Kano State, Nigeria. The minimum sample size for this study was 232 lecturers. The respondents were selected based on a proportionate stratified random sampling technique. The data was collected using an adapted questionnaire containing the respondent profile, ICT usage, and the six selected factors above. Descriptive statistics, including frequencies, percentages, mean, and standard deviation were applied to describe the respondent profile and their ICT usage level, as well as and the related factors of ICT usage. Meanwhile, inferential statistics including Analysis of Variance (ANOVA), correlation analysis, and logistic regression were employed to compare the mean scores, to determine the relationship between the variables, and to identify the extent of the influencing factors of ICT usage. The findings revealed that more than half of the lecturers had a low ICT usage level; therefore, relevant stakeholders are recommended to take all the possible means to improve ICT usage among Kano State lecturers, as this action could eventually impact the teaching and learning processes in various institutions in Nigeria. This step should be done while considering the factors that relate to the ICT usage of the lecturers surveyed in this study.